Determination of Optimum Cultural Conditions for the Production of Cytosine Deaminase From Escherichia coli - Al-Maeny, S. A. L.; Mohmmad, A. M.; Majeed, I.y.; Ali, A.H . (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study involved isolation and characterization of E.coli from patient’s infected with diarrhea , in order to study the ability of the bacteria to produce cytosine deaminase (CD). Result showed eight isolates of E.coli which showed adifference in the production of (CD) and the isolate of E. coli E33 was the beast of its production of CD than the other’s and the value of the specific activity was 4.920 u/mg protein , when grown in the medium which contains 1% glycerol ,3% peptone as a source of Carbon and Nitrogen respectively with pH 8. The optimum cultural condition‘s for the production of CD from E. coli E33 was studied the result‘s showed that the isolate gave the highest production of the enzyme(5.28 u/mg protein) which was grown in amedium containing 1% glucose as a carbon source while the best source of nitrogen was peptone in conc. 3% and Yeast extract in conc. 0.2%. The initial optimal pH in the production of this enzyme was 8 at 37 C ْ ◌ .